Ethnography of Communication in the Besentulak Tradition: A SPEAKING Model Analysis of the Dynamics of Cultural Communication among the Sasak Community in Jerowaru Village - Muhammad Arkan Anshori; Abdul Malik; Moh. Fakhri (International Journal of Sociology of Religion, 2026)
This article aims to analyze how the ethnography of communication operates within the besentulak tradition in Jerowaru Village, as one of the collective communication practices of the Sasak community that has become deeply rooted in local social and cultural life. This study not only focuses on the external form of the tradition, but also examines the communicative dimensions embedded within each stage of the ritual process, ranging from the determination of the setting, participant involvement, to the mechanism of ritual closure. Amid the currents of modernization, the communicative meanings contained in local traditions often receive limited scholarly attention. Therefore, this research seeks to uncover the structure of cultural communication operating within the tradition. This study employs a descriptive qualitative approach using the ethnography of communication method. The besentulak tradition serves as the primary object for understanding the formation of communicative events, which are subsequently analyzed through Dell Hymes’ SPEAKING framework, including setting, participants, ends, act sequences, key, instrumentalities, norms, and genre. The findings reveal that communication within the besentulak tradition operates in a complex manner through the simultaneous interaction of verbal, symbolic, and kinesic forms of communication. The study further demonstrates that the besentulak tradition functions not merely as a customary deliberative forum, but as a meaningful cultural communication system. The tradition plays a significant role in strengthening social integration, transmitting local wisdom values, and reinforcing the collective identity of the Jerowaru community. Thus, this research contributes to the development of ethnography of communication studies by positioning the Sasak local tradition as an important framework for understanding the dynamics of cultural communication in Indonesian society more comprehensively.